REPRESENTATION OF JAVANESE-DUTCH ACCULTURATION IN THE NOVEL BURUNG-BURUNG MANYAR - Darmawan, Almas Rifqi; Renovriska, Melia Dwi (Journal of Language, Literature and Teaching, 2024)
A language that a person uses on a daily basis inside a society is a flexible tool that can change to meet the needs of its users and the times. The Dutch language continues to have a significant influence on post-colonial writing, particularly in novels and romances. Y. B. Mangunwijaya's Burung-Burung Manyar is a well-known work of post-colonial literature. Teto, the protagonist, is at the heart of the narrative, spinning a tale of adolescent infatuation with undertones of colonialism, treachery, retaliation, and disappointment. Readers are given a sense of wonder by the unusual usage of language. Y. B. Mangunwijaya's choice of language in this story is a fascinating example of how Dutch culture is represented. He gives considerable thought to how a Javanese-born individual who speaks Indonesian as their first language may utilize a Dutch phrase. This phenomenon led the author to use linguistic style and diction to delve deeper into this facet. The research's conclusions are as follows: (1) the author of the novel successfully employs and modifies the diction to represent Dutch culture; and (2) the author's consideration of the speaker's context enables the diction to accurately represent Dutch culture through the linguistic interaction of two cultures, Javanese and Dutch.Keywords: Burung-Burung Manyar, culture, stylistics, acculturation.